Loyalty Model On Youth Instant Messaging Brand Usage - Gustiasa, Muhammad; Surayya Ulfa, S.Sos, M.Si, Nurist (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Instant messaging is one of communications service form that are often used by youth and even replace the short messages service (SMS). The widespread use of instant messaging led to many brands competing in Indonesia to get consumers, data from each brand instant messaging describes an increase trend of continuous usage through strategic communications strategy by each brand. In fact, brand switching on brand instant messaging compete does not require cost at all (zero cost). Moreover, consumer behavior tend to complement each other brand instant messaging by use two or more brand instant messaging at the same time. So, the research on consumer loyalty on brand instant messaging use by youth is unique to implement. This research aim is to test the model of brand loyalty on brand instant messaging usage by youth. This quantitative research apply 5 brand instant messaging as research object that test 5 hypothesis with 6 variables which has formulated a consumer loyalty model based on literature review and state of the art that has been explained. Total respondents on this research are 106 persons, primary data are calculated by Structural Equation Model (SEM) through AMOS application. Through validity and reliability test, normality data test, conformance model test, and hypothesis test this research result model of instant messaging brand loyalty consumer that have been complied in the beginning of this research do not fit. From 5 hypothesis only 2 hypothesis that have significant effect The accepted hypothesis on model test on this research is hypothesis 1 that contains variable information exposure of marketing communications strategy (MC) brand instant messaging and variable knowledge level of product attribute (AP) brand instant messaging with significant number 0.002 which appropriate with marketing communication effect theory that imply on product information. The other accepted hypothesis on this model test is hypothesis 5 that contains variable consumer satisfaction level (SAT) and social support perception (SOC) with brand instant messaging consumer loyalty (LOY) with significant number 0.000 which appropriate with expectations confirmation model and social support theory.